Benthic fauna structure in streams of Colombian Andes - VÁSQUEZ-RAMOS, JESÚS MANUEL; REINOSO-FLÓREZ, GLADYS (Revista Colombiana de Entomología, 2012)
Rivers change spatially and temporally in their physical properties and processes and biological communities. Their study is complex because of their heterogeneity, aspect that motivated to do this research in 2010, aimed to determine the composition and structure of macroinvertebrates, taking into account different substrates through an altitudinal gradient in Andean streams. There were 74 taxa distributed in 42 families and 13 orders. The most abundant families were Chironomidae (Diptera), Leptohyphidae, Leptophlebiidae, Baetidae (Ephemeroptera), Hydropsychidae and Glossosomatidae (Trichoptera). The average density of aquatic macroinvertebrates showed no significant differences between seasons and between substrates (P > 0.05, Mann-Whitney U). There were differences in the macroinvertebrate assemblages according to the type of substrate, but not at the level of river sections; subsequently revealed significant differences were later shown between Sand-Gravel / Pebble, and Sand Rock (ANOSIM , R = 0.3894, P < 0.01), but not between streams evaluated (ANOSIM, R = 0.95, P > 0.05). Shannon-Wiener diversity (H) was significantly lower in the sandy substrate with respect to the substrates rock and gravel / pebble (Mann-Whitney U: Zobs  = -2.8 and Zobs  = -3.2, respectively; P < 0.05), while between stations there was no significant difference (Mann-Whitney U: P > 0.05). Altitudinally Chironominae, Orthocladiinae, Tanypodinae, Baetodes, Camelobaetidius, Leptohyphes, Thraulodes and Smicridea were recorded in all stations.